Сімейне право. Шлюбні відносини - Георгієва, Я. В. (ХНУРЕ, 2023)
The report explores the variation in marriage and divorce laws across different countries, emphasizing how cultural, historical, and religious factors shape legal systems. The report highlights the importance of adhering to international human rights standards and ensuring equality before the law for all members of a family, regardless of cultural or religious beliefs. The Ukrainian legislation on family law is briefly discussed as an example of a country with its own specific legal system. Furthermore, the report emphasizes the need for ongoing evaluation and reform of family law systems to ensure they are keeping pace with changing societal norms and values.